2020
DOI: 10.17718/tojde.803360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interactive Video Length Within E-Learning Environments on Cognitive Load, Cognitive Achievement and Retention of Learning

Abstract: The importance of using the interactive video has been widely recognized in e-learning courses. However, there are several variables that can affect learners' engagement and their learning through watching digital interactive videos. the main purpose of this study is to examine whether long interactive videos can improve students' performance in tests, retention of learning in the long term, and reduce the cognitive load compared to medium and short videos. An experimental research was conducted on a sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 40 publications
5
19
0
2
Order By: Relevance
“…Harrison (2015) reports that students demanded instructional videos be shorter than 20 minutes. This finding also coincides resources" is recommended with the purpose of alleviating cognitive burden on the part of students (Afify, 2020). This lack of quality is also related to the length and workload associated with producing them.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Harrison (2015) reports that students demanded instructional videos be shorter than 20 minutes. This finding also coincides resources" is recommended with the purpose of alleviating cognitive burden on the part of students (Afify, 2020). This lack of quality is also related to the length and workload associated with producing them.…”
Section: Discussionsupporting
confidence: 71%
“…Slemmons et al's (2018) finding. Additionally,Lo and Hew (2017) propose 6-minute instructional videos in flipped learning Afify (2020). concludes that short videos (<6 minutes) are effective in terms of increasing student achievement and retention and in reducing cognitive load.…”
mentioning
confidence: 99%
“…Although our qualitative survey did not present comments on this topic, students' assessment could have been influenced by this aspect. Indeed, research has shown that students who watch short videos perform better in terms of cognitive achievement [45]. In this sense, another study found that students prefer watching video content of 5-6 min [46].…”
Section: First Decisionmentioning
confidence: 98%
“…Our literature review revealed that most studies have only examined the effects of incorporating either a single segmentation theory or a single self-explanation theory into an instructional video on learning performance. There is a lack of studies that have examined how design theories using video segmentations affect cognitive load (Afify, 2020). Cognitive load is considered as one of priorities when designing and producing instructional videos as cognitive load is related to students' capacity of processing video information (Sweller et al, 2011).…”
Section: Problems With Instructional Videosmentioning
confidence: 99%